Integration of national and modern experiences in improving reading literacy in primary grades - Yuldasheva, Iroda; Kurbanova, Bakhtikhon Kochkorbayevna (TLEP – International Journal of Multidiscipline, 2025)
This scientific article considers the urgent problem of improving the level of reading literacy of students at the primary education stage, substantiating the scientific and practical importance of combining national pedagogical traditions with internationally recognized modern approaches. The focus of the research is on creating synergy between national experience (for example, the "teacher-student" tradition, methods of teaching classical literature) and modern experience (for example, international assessment criteria such as PISA, PIRLS, integration of digital literacy, interactive methods of developing understanding). The article theoretically and practically substantiates the fact that by combining these two approaches, it is possible to develop not only reading speed and technique, but also the skills of deep understanding of the text, critical thinking and application of the acquired knowledge to real-life situations. The research methodology is based on a combination of qualitative, quantitative and mixed methods, which allows testing the effectiveness of the integration model. The results show that the integrated approach leads to significant positive changes in the level of students’ understanding of the text compared to traditional methods. This work serves to solve the task facing the education system of achieving world standards while maintaining national identity.